Diagnostic Performance of High-Resolution Vessel Wall MR Imaging Combined with TOF-MRA in the Follow-up of Intracranial Vertebrobasilar Dissecting Aneurysms after Reconstructive Endovascular Treatment - Tan, S.; Zhou, X.; Xu, X.; Lu, Y.; Zeng, X.; Wu, Q.; Wang, Y. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Few studies have reported the utility of high-resolution vessel wall MR imaging in the follow-up of endovascularly treated vertebrobasilar dissecting aneurysms. This study aimed to evaluate the diagnostic performance of high-resolution vessel wall MR imaging combined with TOF-MRA in the follow-up of intracranial vertebrobasilar dissecting aneurysms after reconstructive endovascular treatment.MATERIALS AND METHODS: Patients with intracranial vertebrobasilar dissecting aneurysms with reconstructive endovascular treatment and followed up with TOF-MRA, high-resolution vessel wall MR imaging, and DSA were included. With DSA as the criterion standard, the diagnostic performance of TOF-MRA, high-resolution vessel wall MR imaging, and high-resolution vessel wall MR imaging combined with TOF-MRA in the evaluation of aneurysm occlusion status and parent artery patency was assessed. Visualization of the stented artery on TOF-MRA and high-resolution vessel wall MR imaging was rated on a 5-point scale.RESULTS: Twenty-seven patients with 29 aneurysms were included. The sensitivity, specificity, positive predictive value, and negative predictive value of TOF-MRA, high-resolution vessel wall MR imaging, and high-resolution vessel wall MR imaging combined with TOF-MRA for diagnosing aneurysm remnants were 80.0%, 100.0%, 100.0%, and 82.4%; 53.3%, 100.0%, 100.0%, and 66.7%; and 93.3%, 100.0%, 100.0%, and 93.3%, respectively. For the visualization of the stented artery, the mean score of high-resolution vessel wall MR imaging was significantly higher than that of TOF-MRA (4.88 [SD, 0.32] versus 2.53 [SD, 1.25], P < .001). In the evaluation of parent artery patency (normal or pathologic), whereas TOF-MRA had a sensitivity, specificity, positive predictive value, and negative predictive value of 100.0%, 8.0%, 14.8%, and 100.0%, respectively, high-resolution vessel wall MR imaging was completely consistent with the DSA.CONCLUSIONS: High-resolution vessel wall MR imaging combined with TOF-MRA at 3T showed good diagnostic performance in the follow-up of intracranial vertebrobasilar dissecting aneurysms after reconstructive endovascular treatment.EVTendovascular treatmentHR-VW-MR imaginghigh-resolution vessel wall MR imagingIMHintramural hematomaSPACEsampling perfection with application-optimized contrasts by using different flip angle evolutionsVBDAvertebrobasilar dissecting aneurysm